Structural and Thermal Behavior of Meglumine-Based Supra-Amphiphiles in Bulk and Assembled in Water - Ferreira, Leonardo M. B. [UNESP]; Kurokawa, Suzy S. S. [UNESP]; Alonso, Jovan D. [UNESP]; Cassimiro, Douglas Lopes [UNESP]; Ribeiro de Souza, Ana Luiza [UNESP]; Fonseca, Mariana [UNESP]; Sarmento, Victor Hugo V.; Regasini, Luis Octavio [UNESP]; Ribeiro, Clovis Augusto [UNESP] (Amer Chemical Soc, 2016)
Supra-amphiphiles are a new class of building blocks that are fabricated by means of noncovalent forces. In this work, we studied the formation of supra-amphiphiles by combining hydrophilic meglumine (MEG) with hydrophobic maleated castor oils (MACO). Spectroscopic analysis demonstrated that ionic interactions are the main driving force in the fabrication of these materials. Subsequently, supra-amphiphile/water systems were examined for their structure and water behavior by polarized optical microscopy (POM), small-angle X-ray scattering (SAXS), and differential scanning calorimetry (DSC). Micellar and lamellar liquid crystalline phases were observed. Finally, we observed that the supra-amphiphiles produced using an excess of MEG retain a large amount of water. As bound water plays an important role in biointerfacial interactions, we anticipate that these materials will display a pronounced potential for biomedical applications.